It/He/They/She: On Pronoun Norms for All, Human and Nonhuman - Alyse Spiehler; Bob Fischer (Ergo, An Open Access Journal of Philosophy)
Many people in animal studies favor the use of gendered pronouns for nonhuman animals, even in cases where the animal’s sex is unknown. By contrast, many people in gender studies favor the use of the default singular they for humans. Our aim is to show that the most obvious ways of fitting these pronoun norm proposals together—a hybrid option (“he”/“she” for animals, “they” for humans) and a uniform one (i.e., default to the singular they when gender identity is unknown, regardless of species)—have serious costs. Animal advocates will worry that the hybrid approach marks animals as fundamentally different from human beings, while advocates for gender justice will worry that preserving gendered pronouns for animals will also preserve gender essentialism. However, switching to a universal default singular they—that is, where we use “they” for all individuals, both human and nonhuman—may set back animals’ interest in being seen as sentient individuals. Our aim is not to defend a solution to this problem, but simply to argue that this is a problem that deserves consideration when assessing candidate pronoun norms.